Vaccinations/health economy/mumps measles rubella – vaccination issues – health economy study? - O'Mahony, Sarah (2010)
Abstract Background An interest into evidence-based practice (EBP) implementation onto pre-registration nursing courses came from the falsified media hype around the MMR debate and the vast impact this had on society in terms of fear, mistrust of vaccinations and health professionals, and the health implications this also had on children from parents deciding not to vaccinate or choosing monovalent vaccines. The importance of EBP on pre-registration nursing courses is exemplified with the provision of skills to search, critique and disseminate literature to healthcare consumers in order to provide them with information to make the right, personal healthcare choices from best-available evidence. Methods Diploma, degree and masters students in their final year of their pre-registration nursing courses at the University of Nottingham were approached in lectures and asked to complete a questionnaire. Demographics were obtained and students rated the 32 questions on a five point Likert scale. 196 questionnaires of a possible 458 were retrieved. Responses on MMR vaccination safety and perceptions of EBP within the nursing courses were inputted onto SPSS statistical database where percentage responses were collated in terms of branch, course and cohort and p-values were calculated for mainly course comparisons. Results There were statistically significant differences between courses in terms of perceived MMR vaccine safety, which showed masters students, had greater confidence (p=0.021). Diploma and degree students had greater confidence in nurses practicing EBP (p=0.001) and basing healthcare decisions on EBP (p=0.000), however degree and diploma students’ knowledge came mainly from the media, more so than masters students (p=0.027). Conclusion Whilst there are positive responses in terms of perceived MMR safety and EBP, students lack important comprehensive skills in critiquing research and implementing this in practice. As a professional, there is a need to provide consumers with best available evidence in order to make informed health choices.